PENGARUH KESIAPAN ORGANISASI DAN PERUBAHAN STRUKTUR ORGANISASI TERHADAP KINERJA UMKM DENGAN TRANSFORMASI DIGITAL SEBAGAI VARIABEL MEDIASI PADA UMKM KULINER DI CIKARANG BARAT - Rani Indriani; Siti Aswah; Helga Betty Deviyanti; Mohammad Mozart; Aulia Ananta Nurrochim (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study aims to examine the impact of organizational readiness and changes in organizational structure on the performance of culinary SMEs in West Cikarang, with digital transformation as a mediating variable. This study employs a quantitative approach, using a questionnaire distributed to 100 respondents, including owners and employees of culinary SMEs, as the data collection method. Sampling was conducted using random selection, and data analysis employed the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method via the SmartPLS software. The findings of this study indicate that organizational readiness has a positive and significant impact on digital transformation, as do changes in organizational structure, which also contribute positively and significantly to digital transformation. Furthermore, digital transformation was found to have a positive and significant impact on SME performance. However, no significant direct influence of organizational readiness or organizational structural changes on performance was found. Moreover, digital transformation can serve as a mediator between organizational readiness, organizational structural changes, and SME performance. These results confirm that improving the performance of culinary SMEs is more effectively achieved through strengthening digital transformation supported by organizational readiness and a flexible organizational structure.